Soil chemical properties related to acidity under successive pig slurry application - Lourenzi,Cledimar Rogério (2011)
Pig slurry application as soil manure can alter the chemical properties of the soil and affect its acidity, modifying the environment for crop growth and development. The objective of this study was to evaluate the chemical properties related to soil acidity subjected to successive applications of pig slurry. The experiment was conducted in May 2000, in an experimental area of the Federal University of Santa Maria (UFSM) under no-tillage and lasted until January 2008. Nineteen surface applications of 0, 20, 40, and 80 m³ ha-1 of pig slurry were performed, during a period of 100 months and the soil sampled in the end (layers 0-2, 2-4, 4-6, 6-8, 8-10, 10-12, 12-14, 14-16, 16-18, 18-20, 20-25, 25-30, 30-35, 35-40, 40-50 and 50-60 cm). The application of pig slurry increased soil pH values, an effect that could reach the depth of 8 cm without affecting the potential acidity values. The applications also resulted in accumulation of Ca and Mg exchangeable levels in the surface layers, increasing base saturation and reducing Al saturation. Long-term applications induced an increase in organic matter in the deeper layers. However, the effect of this residue on the potential CEC was less significant and restricted to the surface layers.